The layers of Canada - Rahman, Mehnaz Abdul; Steele, Claudia Magalhaes; Francis, Josée; Stefan, Bailey (My University, 2020)
“The Layers of Canada” podcast episode uses storytelling and ethnography to explore the origins and essentials of fashion in Treaty 6 Territory. How does one look professional in brutal temperatures? How are Canadian winters so paradoxically dark and bright? How do new and Indigenous Canadians make Canadian fashion while negotiating dressing for the weather as an act of culture and a matter of survival? Research and Narration by Mehnaz Abdul Rahman, Claudia Magalhaes Steele, Josée Francis. Scripting, Editing and Narration by Bailey Stefan. Created for BCSC 302 Multimedia.
Keywords: fashion; winter; Canada; storytelling